Hydrolytic degradation and biodegradation of polylactic acid electrospun fibers - Soo, Debbie Xiang Yun (2024)
Increased use of bioplastics, such as polylactic acid (PLA), helps in reducing greenhouse gas emissions, decreases energy consumption and lowers pollution, but its degradation efficiency has much room for improvement. The degradation rate of electrospun PLA fibers of varying diameters ranging from 0.15 to 1.33 μm is measured during hydrolytic degradation under different pH from 5.5 to 10, and during aerobic biodegradation in seawater supplemented with activated sewage sludge. In hydrolytic conditions, varying PLA fiber diameter had significant influence over percentage weight loss (W%L), where faster degradation was achieved for PLA fibers with smaller diameter. W%L was greatest for PLA-5 > PLA-12 > PLA-16 > PLA-20, with average W%L at 30.7%, 27.8%, 17.2% and 14.3% respectively. While different pH environment does not have a significant influence on PLA degradation, with W%L only slightly higher for basic environments. Similarly biodegradation displayed faster degradation for small diameter fibers with PLA-5 attaining the highest degree of biodegradation at 22.8% after 90 days. Hydrolytic degradation resulted in no significant structural change, while biodegradation resulted in significant hydroxyl end capping products on the PLA surface. Scanning electron microscopy (SEM) imaging of degraded PLA fibers showed a deteriorated morphology of PLA-5 and PLA-12 fibers with increased adhesion structures and irregularly shaped fibers, while a largely unmodified morphology for PLA-16 and PLA-20.